Dominican Republic Gearing Up for a More Efficient Tax System : An Assessment of Tax Efficiency, a Cost-Benefit Analysis of Tax Expenditures, and an Exploration of Labor Informality and its Tax Implications - World Bank (World Bank, Washington, DC, 2018)
This study discusses options how to increase the Dominican Republic tax revenue and attempts to identify priority areas for efficiency-enhancing reforms. A 2016 World Bank report on Dominican fiscal policy found that the country's tax expenditures were poorly targeted and regressively distributed, benefitting the wealthy more than the poor, and imposed considerable fiscal and economic costs. The report also showed that the tax contribution of the informal sector is extremely low, despite the fact that informal workers account for roughly half of the active labor force. As the new government prepares the ‘fiscal pact' first described in the country's development strategy 2030, policymakers will require a more thorough understanding of these issues and their fiscal, economic, and distributional implications. Thus, building on past analytical work, the present study focuses on two priority areas: tax efficiency and labor informality. Chapter One reveals that the DR's strong and sustained economic growth in recent years has had only a modest impact on revenues' efficiency from value-added tax, corporate income tax, personal income tax, and minor taxes. An analysis of tax-collection efficiency reveals several feasible options for boosting tax revenues. Chapter Two explores the characteristics, correlates, and effects of widespread labor informality in the DR. Identifying the correlates of informality yield important implications for promoting formalization and thereby broadening the income-tax base.